Lumbosacral plexopathy due to pelvic hematoma after extracorporeal membrane oxygenation: A case report. Issue 17 (30th April 2021) - Wilks, Anson W.; Al-Lozi, Muhammad T.
Abstract: Rationale: Peripheral nerve injury related to vascular complications associated with extracorporeal membrane oxygenation (ECMO) is perhaps underappreciated. Compared to the well-described central nervous system complications of ECMO, brachial plexopathy and lumbosacral plexopathy have rarely been reported. We report this case to heighten awareness of lumbosacral plexus injury due to pelvic hematoma formation after ECMO. Patient concerns: A 53-year-old woman developed a large pelvic hematoma with significant mass effect on intrapelvic structures after receiving lifesaving venoarterial ECMO for cardiogenic shock following a cardiac arrest. During her hospital course, she developed bilateral foot drop that was attributed to critical illness. Her lack of neurological recovery after 6 months prompted referral to neuromuscular medicine for consultation. Diagnosis: The patient was retrospectively diagnosed with bilateral lumbosacral plexopathy due to the large pelvic hematoma. Intervention: Electromyography/nerve conduction study (EMG/NCS) obtained at the time of referral to neuromuscular medicine localized her neurological deficits to the bilateral lumbosacral plexus and demonstrated no volitional motor unit action potentials in her lower leg muscles. Outcomes: The patient had minimal recovery of strength at the level of the ankles but was ambulatory with solid ankle–foot orthoses due to spared proximal lower extremity strength. Unfortunately, the absence of any volitionally activated motor unit action potentials in her lower leg muscles on EMG performed 6 months after the initial injury was a poor prognostic indicator for successful reinnervation and future neurological recovery. Lessons: Neurological deficits occurring during the course of administration of ECMO require accurate localization. Neurology consultation and/or EMG/NCS may be useful if localization is not clear. Lesions localizing to the lumbosacral plexus should prompt radiographic evaluation with computed tomography of the abdomen and pelvis. Hemostasis of a retroperitoneal hematoma may be achieved with embolization. However, if neurological deficits do not improve, surgical consultation for hematoma evacuation may be warranted.